Systematic review on the measurement properties of patient-reported outcome measures (PROMs) for measuring well-being in young children - Paulin Grace Morato-Espino; Jose Ma Rafael Ramos; Ivan Neil Gomez (BMJ Open)
Objective This systematic review aims to summarise and assess the measurement properties of existing instruments for measuring child well-being.Design A systematic review of measurement properties following the COnsensus Based Standards for the Selection of Health Measurement Instruments (COSMIN) guideline and the Joanna Briggs Institute methodology was performed.Data sources A search was performed in PubMed, Medline Complete, CINAHL Plus, Psychology & Behavioral Sciences (via EBSCOHost) and GoogleScholar (last search August 2024).Eligibility criteria This review focused on studies that evaluated the measurement properties of instruments to measure the well-being of children ages 2–7 years, published between 2000 and 2023. We excluded studies that used the child well-being instrument as an outcome measure or to validate another instrument.Risk of bias and data synthesis The methodological quality of eligible studies was evaluated using the COSMIN Risk of Bias checklist, the measurement properties of the instruments per study were assessed using the updated criteria for good measurement properties and an overall rating for the measurement property of each instrument is determined and compared against the criteria for good measurement properties. The quality of evidence was evaluated using the modified Grading of Recommendations Assessment, Development and Evaluation approach, and measurement recommendations were formulated. Results were presented using a narrative synthesis and tables.Results Three measures from three studies were included, and they presented moderate to high quality evidence for structural validity, internal consistency and construct validity. However, limited evidence was available for content validity.Conclusion Few instruments to measure the well-being of children aged 2–7 years are available, and only three measurement properties were fully evaluated in these studies. This review was conducted even if there was incomplete or unavailable information regarding their content validity. Further research is recommended before these measures may be recommended for use.Prospero registration number CRD42023428953.